2012
DOI: 10.1177/230949901202000320
|View full text |Cite
|
Sign up to set email alerts
|

Non-Contrast Magnetic Resonance Imaging for Diagnosing Shoulder Injuries

Abstract: purpose. To compare preoperative non-contrast magnetic resonance imaging (MRI) with arthroscopy findings in diagnosing labral and rotator cuff tears. Methods. 86 men and 60 women aged 21 to 70 (mean, 52) years underwent non-contrast MRI before arthroscopic operations on the glenohumeral joint. Slices were made in a transvese, parasagittal, and paracoronar orientation. The sequences used were T2-and proton-weighted for paracoronar imaging, T1-and T2-weighted for transverse and parasagittal imaging, and T2-weigt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“… 7 This discrepancy may be related to the fact that noncontrast MRI, as used in our study, is not considered the gold standard for diagnosing SLAP tears. 3 , 6 …”
Section: Discussionmentioning
confidence: 99%
“… 7 This discrepancy may be related to the fact that noncontrast MRI, as used in our study, is not considered the gold standard for diagnosing SLAP tears. 3 , 6 …”
Section: Discussionmentioning
confidence: 99%
“… 2 , 4 , 14 , 17 , 34 , 35 However, other studies have demonstrated that noncontrast MRI and MR arthrography are neither highly sensitive nor specific for the diagnosis of superior labral anterior posterior (SLAP) lesions. 1 , 3 , 7 , 15 , 26 , 28 …”
mentioning
confidence: 99%
“…2,4,14,17,34,35 However, other studies have demonstrated that noncontrast MRI and MR arthrography are neither highly sensitive nor specific for the diagnosis of superior labral anterior posterior (SLAP) lesions. 1,3,7,15,26,28 Initially thought to be an uncommon entity, the incidence of SLAP lesion surgery has increased in the United States in the past decade. 23,34,36,38 Such studies have demonstrated that a significant contingent of patients undergoing SLAP lesion surgeries were middle-aged.…”
mentioning
confidence: 99%
“…The diagnostic performance of non-contrast MRI in superior labral tears has been studied several times, with variable results in terms of accuracy and sensitivity [24,25]. While some studies have reported high diagnostic accuracy for MR arthrography, others have demonstrated non-specific as well as non-sensitive results for MRI and MR arthrography in the diagnosis of SLAP lesions [26][27][28]. Early degenerative changes usually cannot be detected with conventional morphological MRI sequences; however, functional sequences such as delayed gadolinium-enhanced MRI of cartilage (dGEMRIC), T2* mapping, and T2 mapping allow the assessment of the biochemical composition of joint structures [29][30][31].…”
Section: Introductionmentioning
confidence: 99%